875Association between dietary inflammatory index and sleep duration. (2nd September 2021) - Melaku, Yohannes Adama; Appleton, Sarah; Reynolds, Amy; Gill, Tiffany; Adams, Robert
Abstract: Background: Diet and sleep are strongly and bidirectionally linked. This study aims to assess the association between dietary inflammatory index (DII) and sleep duration using the National Health and Nutrition Survey (NHANS) of the United States. Methods: A total of 27, 999 (median age 47 years, 48.6% male) participants were included. Dietary data were collected using 24-hour recall method and DII was calculated using 27 nutrients. Quantiles of DII were constructed (quantile 1, least inflammatory; quantile 5, most inflammatory). Self-reported habitual sleep duration was categorized as ≤ 6 hr (short sleep), ≥7 hr (normal/long sleep). We used log-binomial and multinomial logistic regression, adjusted for potential confounders, to examine the association between DII and short sleep duration. Sensitivity analysis was performed by excluding common chronic diseases. The analyses were adjusted using NHANES sampling weights. Results: In the fully adjusted model, higher DII score was associated with shorter sleep duration [odds ratio (OR)quartile2vs1 =1.04; 95% confidence interval (CI): 0.84-1.29; ORquartile3vs1 =1.27; 95% CI: 1.06, 1.52; ORquartile4vs1 =95% CI: 1.47; 95 CI: 1.25, 1.74; ORquartile5vs1 =1.62; 95% CI: 1.33, 1.97; P for trend<0.0001]. A similar trend of association was observed with long sleep duration and in both male and female participants. Participants in the fifth quantile, compared to those in the first, on average had 6 minutes (95% CI: 1, 11) less sleep. Conclusions: Pro-inflammatory diet was positively associated with increased odds of short sleep duration. Key messages: Patients with short sleep duration may benefit from avoiding pro-inflammatory foods. The association between DII and sleep duration could be bidirectional.